IMPLEMENTATION OF THE SPONGE BALL GAME TO IMPROVE DOWN PASSING IN VOLLEYBALL CLASS V MIN 3 SRAGEN TANON DISTRICT SRAGEN REGENCY 2019/2020 ACADEMIC YEAR - Hajar Danardono; Joko Sulistiyono; Erwin Rostandi, (Journal Of Indonesia Sport Education and Adapted Physical Education (JISEAPE), 2022)
This research aims to improve the learning outcomes of basic lower passing movements in volleyball by applying sponge balls to students in class V MIN 3 Sragen, Tanon District, Sragen Regency. This research is Classroom Action Research (PTK). This research was carried out in two cycles, with each cycle consisting of planning, implementing actions, observing and reflecting. The subjects of this research were students of V MIN 3 Sragen, Tanon District, Sragen Regency, 2019/2020 academic year, totaling 30 students consisting of 18 male students and 12 female students. Data sources come from teachers, students and researchers. Data collection techniques are tests and observations.The results of this research show that through the application of sponge ball games to improve bottom passing in volleyball from Pre-Cycle to Cycle I and from Cycle I to Cycle II. Based on the results of this research data analysis, the initial condition of psychomotor students was 59.17%, cognitive 63.12%, affective 63.34% from a total of 30 students, in the first cycle the results of psychomotor students were 71.04%, cognitive 67 .08%, affective 74.16% of the total of 30 students and the second cycle results from Psychomotor students were 84.37%, cognitive 71.87%, affective 80.20% of the total of 30 students. The conclusion of this research is that the application of sponge balls can improve learning outcomes for bottom passing in class V MIN 3 Sragen students in the 2019/2020 academic year.